REPAIR OF SCIATIC NERVE LESION AUGMENTED WITH AMNION MEMBRANE COMPOSITE AND MESENCHYMAL STEM CELL - Heri Suroto; R. Taufan Mulyo Wibisono (Journal Orthopaedi and Traumatology Surabaya)
Background: Peripheral nerve injuries (PNI) are quite common, with an incidence of 13.9% per 100,000 people per year. The most cause is direct penetrating trauma. PNI will cause a significant decrease in the quality of life of patients.